Nasal Cavity Malignant Solitary Fibrous Tumor: A Case Report - Rahul Mahawar; Y. Sobita Devi; Hari Rai; Nilima Devi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2022)
A solitary fibrous tumor (SFT) is a soft tissue sarcoma that arises from soft tissue cells and can arise anywhere in the body. Their incidence is less than 2% of all soft tissue masses. They are generally found in the pleural cavity, but sometimes extra-thoracic sites are also involved. Malignant SFTs of the nasal cavity are very rare. The paper reports a case of a 58-year-old male patient with complaints of left nasal blockage and mass. The patient underwent Functional Endoscopic Sinus Surgery (FESS), and the excised mass was sent for histopathological examination, which showed features consistent with malignant solitary fibrous tumor with CD34, CD99, and BCL2 positive. The patient was started on Adjuvant chemotherapy, has received 2 cycles of chemotherapy, and is currently under treatment.